PEMANFAATAN BERBAGAI JENIS PATI SEBAGAI SUMBER KARBON UNTUK PRODUKSI a-AMILASE EKSTRASELULER Bacillus sp SW2 - Trismilah, Trismilah; Wahyuntari, Budiasih (Badan Pengkajian dan Penerapan Teknologi, 2009)
Currently enzymes become a need of food and non-food industries. Alpha amylase (a-1,4 glucanohydrolase, EC 3.2.1.1) is an enzyme that hydrolyses starch into oligosaccharides and dextrin. The enzyme has been commercially available which mostly produced by Bacillus spp. The bacterium used in thisexperiment was Bacillus sp SW2, which was isolated from Composting Unit at Bumi Serpong Damai, Tangerang. The aim of this experiment was to find the most appropriate starch as an carbon source for enzyme production. The starches observed were tapioca, potato, and cornstarch at concentration of5%. The fermentation was conducted in shaking incubator, in 125 ml Erlenmeyer at 60°C, various pHs, and agitations. The pHs observed were 6, 7.5, 8 and 9 while the rates of agitation applied were 150, 200, and 250 rpm. The results showed that the highest enzyme activity was 20.99 Unit/ml, whichwas reached after 42 hours of fermentation using cornstarch, pH 8 and 200 rpm agitation.